Rethinking the psychology of childhood: Burman, E (1994) Deconstructing developmental psychology. London: Routledge. - Gibson, Kerry (PINS-Psychology in Society, 2026)
Burman’s aim in this text is to offer a deconstructionist critique of developmental psychology. Within this she assesses the broad trends not only in academic research based on developmental theory but also on the practices and social policies that interpret and, sometimes, misinterpret these. This is a daunting challenge, firstly because the scope of developmental theory is so vast, both within its traditional academic boundaries, but even more so if one considers the range of practices in psychology, education, child-care and informal relationships which are characterised by a vision of the child based on principles of developmental psychology. Burman cautiously defines her discussion as introductory, but it nevertheless covers the mainstream research findings in social, emotional, cognitive, language and moral development as well as the common sense understandings which overlap with these. In each area she refers to mainstream findings, considers research which challenges these and supplements existing critiques with her own deconstructionist insights.